Given: sin(3x) / sin(x) - cos(3x) / cos (x) = 2
To prove this, we manipulate the left-hand side (LHS) of the given equation to reach the right-hand side. That is:
LHS = sin(3x) / sin(x) - cos(3x) / cos (x)
= [ sin(3x) cos(x) - cos(3x) sin (x) ] / [ sin(x) cos(x) ].
=sin(3x - x) / [ sin(x) cos(x) ] by applying difference of two angles identity for sine function
=sin(2x) / [ sin(x) cos(x) ] by simplification
= [ 2 sin(x) cos(x) ] / [ sin(x) cos(x) ] by double-angle identity for sine function
= 2 [ sin(x) cos(x) ] / [ sin(x) cos(x) ] by factoring
= 2 by cancellation
= RHS.
This shows that sin(3x) / sin(x) - cos(3x) / cos (x) = 2.
2006-10-27 16:48:46
·
answer #1
·
answered by rei24 2
·
1⤊
0⤋
sin2x = sin(3x-x) = sin3xcosx - sinxcos3x (1)
sin2x = 2sinxcosx (2)
(1) = (2) then
2sinxcosx = sin3xcosx - sinxcos3x
if sinxcosx <>0 then
2 = [sin3xcosx - sinxcos3x] / sinxcosx
2 = sin3x/sinx - cos3x/cosx
Voila.
2006-10-27 16:36:13
·
answer #2
·
answered by Dr. J. 6
·
0⤊
0⤋
hello. ok here's my answer.
sin3x/sinx - cos3x/cosx
= [(sin 3x cos x) - (cos 3x sin x)] / sin x cos x
But we know using the compound angle formulae
sin (3x - x ) = (sin 3x cos x) - (cos 3x sin x)
therefore, sin 2x = (sin 3x cos x) - (cos 3x sin x)
subtituting it back into the equation,
sin3x/sinx - cos3x/cosx
= sin 2x/ six cox
= 2sin 2x / 2sin x cos x
= 2sin 2x / sin 2x
= 2 ( shown )
hope i helped. Good Luck !!!
2006-10-27 16:55:36
·
answer #3
·
answered by Nirmal87 2
·
0⤊
0⤋
Multiply both sides by sin x cos x:
sin 3x cos x - cos 3x sin x = 2 sin x cos x
2 sin x cos x = sin 2x
and, from the identity sin(A-B) = sin A cos B - cos A sin B, with A=3x and B=x, you get
sin 3x cos x - cos 3x sin x = sin(3x-x) = sin 2x
so both sides are equal.
2006-10-27 16:30:02
·
answer #4
·
answered by James L 5
·
0⤊
0⤋
Do you know the formula e(ix) = cos(x) + i*sin(x)? It's very useful for solving these types of problems. You can derive all sorts of relationships with it. In your case e(3ix) = cos(3x) + i*sin(3x) But it's also equal to (e(ix))^3 = (cos(x) + i*sin(x))^3 = cos^3(x) + 3i*cos^2(x)sin(x) - 3cos(x)sin^2(x) - i*sin^3(x) Now compare real and imaginary terms cos(3x) = cos^3(x) - 3cos(x)sin^2(x) sin(3x) = 3cos^2(x)sin(x)-sin^3(x) Now simply substitute: (3cos^2(x)sin(x)-sin^3(x))/sin(x) - (cos^3(x) - 3cos(x)sin^2(x))/cos(x) =3*(sin^2(x)+cos^2(x)) - (sin^2(x)+cos^2(x)) =3-1 = 2
2016-05-22 02:18:49
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
sin3x/sinx-cos3x/cosx=sin(2x+x)/sinx -cos(2x+x)
sin2x=
2006-10-27 16:42:35
·
answer #6
·
answered by peterwan1982 2
·
0⤊
0⤋